Different Roles for the Axin Interactions with the SAMP versus the Second Twenty Amino Acid Repeat of Adenomatous Polyposis Coli - Schneikert, Jean; Ruppert, Jan Gustav; Behrens, Jürgen; Wenzel, Eva Maria (PLoS ONE, 2014)
Wnt signalling is prevented by the proteosomal degradation of ?-catenin, which occurs in a destruction complex containing adenomatous polyposis coli (APC), APC-like (APCL), Axin and Axin2. Truncating mutations of the APC gene result in the constitutive stabilisation of ?-catenin and the initiation of colon cancer, although tumour cells tolerate the expression of wild-type APCL. Using the colocalisation of overexpressed Axin, APC and APCL constructs as a readout of interaction, we found that Axin interacted with the second twenty amino acid repeat (20R2) of APC and APCL. This interaction involved a domain adjacent to the C-terminal DIX domain of Axin. We identified serine residues within the 20R2 of APCL that were involved in Axin colocalisation, the phosphorylation of truncated APCL and the down-regulation of ?-catenin. Our results indicated that Axin, but not Axin2, displaced APC, but not APCL, from the cytoskeleton and stimulated its incorporation into bright cytoplasmic dots that others have recognised as ?-catenin destruction complexes. The SAMP repeats in APC interact with the N-terminal RGS domain of Axin. Our data showed that a short domain containing the first SAMP repeat in truncated APC was required to stimulate Axin oligomerisation. This was independent of Axin colocalisation with 20R2. Our data also suggested that the RGS domain exerted an internal inhibitory constraint on Axin oligomerisation. Considering our data and those from others, we discuss a working model whereby ?-catenin phosphorylation involves Axin and the 20R2 of APC or APCL and further processing of phospho-?-catenin occurs upon the oligomerisation of Axin that is induced by binding the SAMP repeats in APC.
EVALuna2:10306